2015
DOI: 10.1037/a0038204
|View full text |Cite
|
Sign up to set email alerts
|

Children with autism do not show sequence effects with auditory stimuli.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Connor, 1970;Rimland, 1964;Scheerer, Rothmann, & Goldstein, 1945). Some researchers have suggested that such difficulties may underpin or exacerbate difficulties processing social information (Gastgeb, Strauss, & Minshew, 2006;Klinger & Dawson, 1995). For example, a father struggled to teach his son with autism to stay away from strangers (Klinger & Dawson, 1995). Nosofsky, 1986) reported no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…1d). Yet, in line with previous studies 11,[19][20][21] , the magnitude of the bias was significantly smaller in both the ASD and the dyslexia groups compared with their corresponding, matched neurotypical groups (two sample t-tests; 56 = 2.07, = 0.04, presented sequentially, with a quiet inter-stimulus-interval (ISI). Participants then decided whether the 1 st or 2 nd tone had a higher pitch by pressing "1" or "2" and received a visual feedback.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…1d). Yet, in line with previous studies 11,[19][20][21] , the magnitude of the bias was significantly smaller in both the ASD and the dyslexia groups compared with their corresponding, matched neurotypical groups (two sample t-tests; 56 = 2.07, = 0.04, presented sequentially, with a quiet inter-stimulus-interval (ISI). Participants then decided whether the 1 st or 2 nd tone had a higher pitch by pressing "1" or "2" and received a visual feedback.…”
Section: Resultssupporting
confidence: 86%
“…Indeed, there are theoretical reasons to expect non-linear longer-term dependence 16 . Yet, previous studies have only used linear methods 11,17,21,23,26 . To study the bias with non-linear modeling, we conducted a new experiment online via the Mechanical Turk platform (Materials and Methods;…”
Section: Neurotypical Bias Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date, the evidence for this hypothesis has been mixed. On the one hand, the results of some of the studies support the hypo‐priors account, for example, Goris et al [] found that individuals with ASD are less flexible in modulating their predictions, while Molesworth et al [] reported decreased effect of prior experience in the form of sequence effects on categorization. Similarly, Turi et al [] found reduced adaptation to numbers, which the authors explain in terms of decreased use of past experience on current perceptual decisions.…”
Section: Decreased Use Of Prior Knowledge In Perception In Autismmentioning
confidence: 94%
“…Hence, weaker (i.e., lower precision or less confidence in) top-down predictions would also lead to increased reliance on bottom-up information as in the ''weak priors" account (Pellicano & Burr, 2012). The importance of relative precisions, however, also implies that studies that find reduced adaptation in behavior or reduced repetition suppression in fMRI responses in ASD (or high autism traits) (e.g., Ewbank et al, 2014;Molesworth, Chevallier, Happé, & Hampton, 2015;Turi et al, 2015) cannot simply be considered evidence for the weaker priors thesis, even though both adaptation and repetition suppression are thought to be the result of (top-down) predictive activity (Chopin & Mamassian, 2012;Summerfield, Trittschuh, Monti, Mesulam, & Egner, 2008).…”
Section: Introductionmentioning
confidence: 89%